THEORETICAL AND PRACTICAL BASIS OF DEVELOPING PROFESSIONAL SPIRITUAL CULTURE IN FUTURE PRESCHOOL EDUCATIONAL ORGANIZATIONS' TEACHERS (Universal International Scientific Journal, 2026)
The article analyzes the conceptual foundations of the development of professional spiritual culture in future educators of preschool educational organizations from a scientific, theoretical and practical perspective. The research used the methods of analysis of theoretical literature, survey, interview, observation, case analysis and role-playing games, and the data were analyzed using descriptive and statistical methods. This study combines theoretical, practical and social approaches and is aimed at identifying effective areas for the formation of professional spiritual culture of educators. The results of the study show that the personal and professional development of the educator, moral and emotional stability, as well as the spiritual and moral development of children, have a direct impact on
Keywords: professional spiritual culture; educator; preschool education